An Approach Towards a FEP-based Model for Risk Assessment for Hydraulic Fracturing Operations. (November 2016) - Gläser, D.; Dell'Oca, A.; Tatomir, A.; Bensabat, J.; Class, H.; Guadagnini, A.; Helmig, R.; McDermott, C.; Riva, M.; Sauter, M.
Abstract: We consider an exemplary scenario drafted in the context of the recently started EU-project FracRisk. The setting belongs to six scenarios representing diverse subsurface processes on different scales. A numerical approach considering sources, pathways and targets quantifies the environmental impact associated with this setting. A Global Sensitivity Analysis of properly defined output quantities takes into account uncertain parameters and operational conditions within a FEP-based evaluation of risk and counteractive measures. At this early stage of the project, this showcase of the general modeling workflow addresses migration of frac-fluid through a naturally fractured reservoir (source) to an overlying formation (target).